Assessment of mangrove water quality by multivariate statistical analysis in Suppa coast, South Sulawasi, Indonesia - Mohd Ikhwan, Toriman; Amal, Arfan; Zulkifli, Yusop (2013)
Different statistical analysis such as, ANOVA, principal component analysis and multidimensional scale plot were employed to evaluate the trophic status of water quality for three monitoring stations. The present study was carried out to determine the physicochemical parameters of mangrove water of Suppa coast, Pinrang South Sulawesi, Indonesia during September 2011 - April 2012. Seasonal variations of different parameters investigated were as follows: salinity (26.78 - 31.11 ppt), water pH (8.10 - 8.15), substrate pH(5.81 - 6.041), water temperature (29.22 - 30.92), dissolved oxygen (3.37 - 3.89 mg/l), biochemical oxygen demand(2.65 - 4.46) and turbidity (5.44 - 10.67 NTU). Salinity, BOD and turbidity indicated a correlation at P<0.05. Based on the test ANOVA, salinity, water pH, water temperature, DO, BOD and turbidity displayed significant seasonal variation (P< 0.05), while substrate pH displayed significant seasonal variation (P> 0.05). PCA and MDS identified the spatial and temporal characteristics of trophic stations and showed that the salinity, BOD and turbidity may be major driving factors for deteriorating trophic status of water quality in the Suppa mangroves.